Pandopo Catering as a Medium for Student Community Service and Community Empowerment: Pandopo Catering sebagai Media Pengabdian Mahasiswa dan Pemberdayaan Masyarakat - Budi Djatmiko; Abshor Marantika; Muhamaad Rifat Syauqy; Sudadi Pranata; Lista Meria; Cicilia Sriliasta Bangun (ADI Publisher, 2025)
This community service project examines the role University of Raharja students in community service, focusing on efforts to foster social awareness and economic independence through the introduction of